Regolith breccia Northwest Africa 7533: Mineralogy and petrology with implications for early Mars. (25th October 2016) - Hewins, Roger H.; Zanda, Brigitte; Humayun, Munir; Nemchin, Alexander; Lorand, Jean‐Pierre; Pont, Sylvain; Deldicque, Damien; Bellucci, Jeremy J.; Beck, Pierre; Leroux, Hugues; Marinova, Maya; Remusat, Laurent; et al.
Abstract: Northwest Africa 7533, a polymict Martian breccia, consists of fine‐grained clast‐laden melt particles and microcrystalline matrix. While both melt and matrix contain medium‐grained noritic‐monzonitic material and crystal clasts, the matrix also contains lithic clasts with zoned pigeonite and augite plus two feldspars, microbasaltic clasts, vitrophyric and microcrystalline spherules, and shards. The clast‐laden melt rocks contain clump‐like aggregates of orthopyroxene surrounded by aureoles of plagioclase. Some shards of vesicular melt rocks resemble the pyroxene‐plagioclase clump‐aureole structures. Submicron size matrix grains show some triple junctions, but most are irregular with high intergranular porosity. The noritic‐monzonitic rocks contain exsolved pyroxenes and perthitic intergrowths, and cooled more slowly than rocks with zoned‐pyroxene or fine grain size. Noritic material contains orthopyroxene or inverted pigeonite, augite, calcic to intermediate plagioclase, and chromite to Cr‐bearing magnetite; monzonitic clasts contain augite, sodic plagioclase, K feldspar, Ti‐bearing magnetite, ilmenite, chlorapatite, and zircon. These feldspathic rocks show similarities to some rocks at Gale Crater like Black Trout, Mara, and Jake M. The most magnesian orthopyroxene clasts are close to ALH 84001 orthopyroxene in composition. All these materials are enriched in siderophile elements, indicating impact melting and incorporation of a projectile component, except for Ni‐poor pyroxene clasts which are from pristine rocks. Clast‐laden melt rocks, spherules, shards, and siderophile element contents indicate formation of NWA 7533 as a regolith breccia. The zircons, mainly derived from monzonitic (melt) rocks, crystallized at 4.43 ± 0.03 Ga (Humayun et al.2013 ) and a 147 Sm‐ 143 Nd isochron for NWA 7034 yielding 4.42 ± 0.07 Ga (Nyquist et al.2016 ) defines the crystallization age of all its igneous portions. The zircon from the monzonitic rocks has a higher Δ 17 O than other Martian meteorites explained in part by assimilation of regolith materials enriched during surface alteration (Nemchin et al.2014 ). This record of protolith interaction with atmosphere‐hydrosphere during regolith formation before melting demonstrates a thin atmosphere, a wet early surface environment on Mars, and an evolved crust likely to have contaminated younger extrusive rocks. The latest events recorded when the breccia was on Mars are resetting of apatite, much feldspar and some zircons at 1.35–1.4 Ga (Bellucci et al.2015 ), and formation of Ni‐bearing pyrite veins during or shortly after this disturbance (Lorand et al.2015 ).